THE EFFECTS OF IS RESOURCES ON AIS CAPABILITIES AND PERFORMANCE OF MALAYSIAN CO-OPERATIVES - Mohd Hadzrami Harun Rasit (International Journal of Accounting, Finance and Business, 2021)
Accounting information systems (AIS) capabilities are essential because of theirability to process business data into useful and timely information according to users’requirements. Indeed, empirical evidences suggested that the use of AIS has positive impact onfirm performance. However, factors that contribute to AIS capabilities and consequentlyimprove co-operative’s performance were not adequately explained. As such, this paper drawson the resource-based view (RBV) to examine the factors that influence AIS capabilities andperformance of Malaysian co-operatives. Using a quantitative approach, questionnaires areused to collect data from 115 co-operative managers across Malaysia. Partial Least Square-Structural Equation Modelling is used to analyse the data. The study found that IS technicalskills, and planning and change management are significant factors that influence AIScapabilities. Theoretically, the study contributes to knowledge by providing an understandingof the roles of IS resources in AIS capabilities building. Also, the study provides support forthe importance of IS resources in AIS capabilities building and improving performance.Practically, the study provides guidelines for co-operatives’ stakeholders, particularlymanagement, in planning and managing their IS resources.